PERSPEKTIF HUKUM KONSUMEN TERHADAP JASA PENGIRIMAN SICEPAT EKSPRES TERKAIT KLAUSULA EKSONERASI DALAM SYARAT-SYARAT DAN KETENTUAN (TERMS AND CONDITIONS) SICEPAT EKSPRES - Yovie Carissa Kumala; Evelyne Juanda T (Universitas Katolik Indonesia Atma Jaya, 2019)
SICEPAT is one of delivery service in Indonesia that located in Jakarta. As the business owner in running its business for its consumer, SICEPAT already prepared every risks that may be occurred one day. Therefore SICEPAT prepared terms and conditions that can be seen by consumers. Inside the terms and conditions point 7, writers saw that SICEPAT included prohibited stipulation by Article 18 paragraph (1) letter a Consumer Protection Law that is written that SICEPAT Ekspres is not responsible if there is a damage, delay and loss to consumer (exoneration clause), this matter according to Article 18 paragraph (3) is stated void by law. The existence of exoneration clause in an agreement will be harmful to consumer. If the consumer experienced loss it means consumer’s rights as written in Article 4 Consumer Protection Law is violated. Therefore consumer has the right to get the compensation. And business owner as written in Article 7 Consumer Protection Law has the obligation that cannot be ignored. Even in Article 19 paragraph (1) Consumer Protection Law clearly stated that business owner must be responsible to give the compensation for the damages, and due to consuming object and/or service that produced or sold by the business owner, the consumer is able to file a report to SICEPAT Ekspres or do the remedy through court or outside the court (BPSK).